Dependency and associated factors among elderly in central Kerala - B., Prithiba; Baskar, Anitha; Lucas, Anupa; S., Rani Suhra; A., Sobha; Devi, Geetha; Philip, Sairu (International Journal Of Community Medicine And Public Health, 2023)
Background: Globally the proportion of elderly has been increasing and physical dependency is one of major problem faced by elderly. Physical dependency will affect the quality of life. Despite this, very limited number of studies were done to assess the dependency among elderly. Aim was to estimate the prevalence of dependency and to determine the association between selected factors and dependency among elderly >60 years. Methods: A cross-sectional study was conducted among 352 elderly in Athirampuzha Panchayat using simple random sampling. A semi-structured interview schedule using basic activities of daily living scale-BADL (Katz scale) was used. Data was coded and entered in Microsoft Excel and analysed using IBM SPSS software version 22. Results: The mean age of participants was 71.68 years with a standard deviation of 8.457 years and the prevalence of dependency was found to be 30.7%. Univariate analysis results revealed that age (>85 years), occupation, living arrangement, presence of aphasia, hearing impairment, visual disturbances, locomotor disability, presence of comorbidity, onset of comorbidity and comorbid conditions like diabetes mellitus, coronary artery disease and chronic arthritis were found to have significant association with dependency. Binary logistic regression results revealed that factors like age group (>85 years), presence of hearing impairment, loco motor disability, onset of comorbidity, presence of diabetes mellitus and coronary artery disease were found to be independent predictors of dependency. Conclusions: Since dependency increases with age physical dependency is to be assessed periodically to achieve healthy ageing.